A retrospective study of clinical characteristics and steroid therapy in immune checkpoint inhibitor-mediated hepatitis - Chuan Jiang; Fei-Lan Yang; Wen-Ting Peng; Ying Li; Shi-Fang Peng; Hui-Min Gu; Lei Fu (Therapeutic Advances in Medical Oncology)
Background: With the widespread clinical application of immune checkpoint inhibitors (ICIs), immune-mediated hepatitis (IMH) has become increasingly prevalent. Objectives: This study aims to analyze the clinical characteristics, steroid treatment, and prognosis of IMH patients, providing further evidence to enhance the safety of ICIs in clinical practice. Design: A retrospective cohort study included tumor patients who received ICI therapy. Comprehensive analyses were conducted to explore the factors influencing the occurrence, clinical characteristics, and prognosis of IMH. Methods: Tumor patients treated with PD-1/PD-L1 inhibitors were enrolled in our study. Patients were stratified based on the occurrence and severity of IMH, as well as the administration of glucocorticoid therapy, to investigate the risk factors for IMH development, critical factors influencing IMH progression, and treatment-specific outcomes. Results: Of 744 patients, 341 (45.8%) developed IMH. IMH was significantly more frequent in females ( p  = 0.001), younger patients ( p  < 0.001), those receiving ICIs with targeted therapy ( p  = 0.009), and patients with hepatocellular carcinoma (HCC; p  < 0.001) or gastric cancer ( p  < 0.001). Coexisting hepatitis B ( p  < 0.001), cirrhosis ( p  = 0.005), and fatty liver disease ( p  = 0.028) were also associated with higher IMH risk. Independent risk factors included female gender, age <45 years, HCC, and gastric cancer. Younger patients were more likely to develop severe IMH ( p  = 0.003). Hepatocellular injury was the most common type of IMH across all grades, with similar risks of severe progression among different IMH types. Glucocorticoid therapy improved outcomes ( p  = 0.011), particularly in grade 3–4 IMH, although no significant difference in outcomes was observed between groups receiving sufficient versus insufficient recommended doses. Conclusion: Female gender, younger age (<45 years), HCC, and gastric cancer are independent risk factors for IMH. Younger patients are more likely to develop severe IMH. Glucocorticoid therapy is beneficial, particularly in grade 3–4 IMH. Early detection, prompt intervention, and tailored management strategies may help mitigate progression and improve outcomes.